Clinical-grade generation of peptide-stimulated CMV/EBV-specific T cells from G-CSF mobilized stem cell grafts - Gary, Regina; Aigner, Michael; Moi, Stephanie; Gottmann, Anja; Maas, Stefanie; Zimmermann, Robert; Zingsem, Jürgen; Strobel, Joachim; Mackensen, Andreas; Mautner, Josef; Moosmann, Andreas; Gerbitz, Armin; et al. (Journal of Translational Medicine, 2018)
BACKGROUND: A major complication after allogeneic hematopoietic stem cell transplantation (aSCT) is the reactivation of herpesviruses such as cytomegalovirus (CMV) and Epstein-Barr virus (EBV). Both viruses cause significant mortality and compromise quality of life after aSCT. Preventive transfer of virus-specific T cells can suppress reactivation by re-establishing functional antiviral immune responses in immunocompromised hosts. METHODS: We have developed a good manufacturing practice protocol to generate CMV/EBV-peptide-stimulated T cells from leukapheresis products of G-CSF mobilized and non-mobilized donors. Our procedure selectively expands virus-specific CD8+ und CD4+ T cells over 9 days using a generic pool of 34 CMV and EBV peptides that represent well-defined dominant T-cell epitopes with various HLA restrictions. For HLA class I, this set of peptides covers at least 80% of the European population. RESULTS: CMV/EBV-specific T cells were successfully expanded from leukapheresis material of both G-CSF mobilized and non-mobilized donors. The protocol allows administration shortly after stem cell transplantation (d30+), storage over liquid nitrogen for iterated applications, and protection of the stem cell donor by avoiding a second leukapheresis. CONCLUSION: Our protocol allows for rapid and cost-efficient production of T cells for early transfusion after aSCT as a preventive approach. It is currently evaluated in a phase I/IIa clinical trial.
EVALuna2:34166

Clotting factor activity in fresh frozen plasma after thawing with a new radio wave thawing device - Kuta, Piotr; Melling, Nathaniel; Zimmermann, Robert; Achenbach, Susanne; Eckstein, Reinhold; Strobel, Joachim (Transfusion, 2019)
BACKGROUND: Massive hemorrhage usually results in rapid need of blood products. Patients in need of fresh frozen plasma (FFP) might benefit from shorter thawing times using a novel radio wave device. So far, only one study on the prototype has been published. Activities of clotting factors after thawing FFP with the radio wave device and with a system using water cushions were compared. This is the first study analyzing the quality of FFP using the fully developed radio wave thawing device UFT100. STUDY DESIGN AND METHODS: Thirty FFP units were thawed with the UFT100 and the Plasmatherm machine. Various clotting factors and inhibitors were analyzed before freezing, immediately after thawing, and after a 48-hour storage period at +4°C. RESULTS: After thawing, all factor activities were within normal ranges regardless of the thawing procedure. We observed significant differences in nearly all clotting factor activities regarding time as effector, whereas thawing with the Plasmatherm machine led to a significant decrease (>10%) only in factor V activity compared to the UFT100. CONCLUSIONS: Immediately after rapid thawing with the UFT100, all FFP units contained adequate coagulation factor activities to maintain hemostatic activity. The UFT100 does not deteriorate FFP quality compared to a conventional system. Regardless of the thawing system, the postthaw refrigerated storage caused a decrease in several clotting factors and inhibitors (factors V, VIII, and IX; von Willebrand factor activity; protein S and C activity) and a significant increase of factor XI.
CRIS-Team Scopus Importer:2019-05-14

Comparison of a new microscopic system for the measurement of residual leucocytes in apheresis platelets with flow cytometry and manual counting - Strobel, Joachim; Antos, U.; Zimmermann, Rüdiger; Eckstein, Reinhold; Zingsem, Jürgen (Vox Sanguinis, 2014)
Since 2001, all blood components in Germany must be leucocyte depleted. Recently, a new method for quality control of depletion was introduced. Our study aimed at the validation of the method for routine use in apheresis platelet concentrates.We compared the new ADAM-rWBC device with manual counting in the Nageotte chamber and flow cytometry, two standard methods, by measuring residual leucocytes in 40 units of apheresis platelet concentrates and in six geometrical dilution series.Cell counts of residual leucocytes in the 40 units were below 10(6) cells per component with all methods, although mean cell counts were approximately 5 and 6 times higher in flow cytometry and ADAM-rWBC, respectively, compared to the Nageotte chamber. No unit with <10(6) leucocytes was regarded as contaminated. The dilution series showed acceptable accuracy, especially in the range around the cut-off (approximately 4·5 cells/?l in components with a volume of 220 ml) for regarding a concentrate as contaminated with leucocytes. No sample spiked with more than 4·5 cells/?l was counted as having less.In comparison with manual counting and flow cytometry, the ADAM-rWBC device performed equally. The method is suitable for routine screening of leucocyte contamination of apheresis platelets.
EVALuna2:15981

Comparison of Simultaneous CD34+ and CD3+ Quantification with a Modified Stem Cell Enumeration Kit on Two Different Flow Cytometers - Strobel, Joachim; Hauck-Dlimi, Barbara; Weisbach, Volker Günter; Eckstein, Reinhold; Zingsem, Jürgen; Strasser, Erwin (Clinical Laboratory, 2016)
BACKGROUND: Quantification of CD34+ cells in peripheral blood stem cell apheresis is normally performed by single platform flow cytometric measurements according to the ISHAGE protocol. Peripheral blood stem cell concentrates (PBSC) produced by apheresis normally contain many T cells. Those T cells can be used for production of donor lymphocyte infusion doses, if abundant amounts of CD34+ cells have been collected. Therefore, it is of interest to know both the CD3+ and the CD34+ cell count of allogeneic PBSC. This is the first study comparing the performance of a modified ISHAGE protocol allowing additional quantification of CD3+ cells on two different flow cytometers, the FACSCalibur and the FACSVerse, respectively. METHODS: CD45+ and CD34+ cell concentrations were measured using a standard and a modified ISHAGE protocol including CD3+ cell quantification on both machines. All cell concentrations were measured using a Trucount bead based stem cell enumeration kit. The FACSVerse machine can additionally be equipped with a sample volume sensor allowing cell quantification without using beads. The samples analysed were taken from granulocyte-colony-stimulating factor mobilized peripheral blood stem cell apheresis procedures (pre- and post-apheresis, and apheresis concentrate). RESULTS: There were no significant differences in cell concentrations measured by the standard and modified ISHAGE protocol, regardless of which machine had been used when using bead quantification. No significant differences between the results of the two flow cytometers using the modified ISHAGE protocol were observed. Pearson´s correlation was always > 0.96, and regression coefficients were higher than 0.93. The only significant differences were observed between bead quantification and volume sensor quantification on the FACSVerse machine. CONCLUSIONS: The modified ISHAGE protocol can effectively be used on both flow cytometers tested, especially if bead quantification is used.
EVALuna2:32774

Comparison of Six Different Cryoprotective Agents Used for Deep Freezing and Storage of CD34+ Cells Derived from Cord Blood and Peripheral Blood Stem Cell Concentrates - Strobel, Joachim; Hohensee, Friederike; Kuta, Piotr; Eckstein, Reinhold; Zingsem, Jürgen (Clinical Laboratory, 2017)
BACKGROUND: For cryopreservation of stem cells, a cryoprotective agent is essential. Dimethyl sulfoxide is commonly used, but has deleterious effects on cell vitality in the warmth and for the recipients of stem cells. The aim of the study was to reduce DMSO and find one cryoprotective solution suitable for stem cells of different origin. Materials: Small volumes of both stem cell apheresis products and cord blood derived stem cells were frozen using six different cryoprotective solutions. Suitability of these solutions was tested by comparing cell vitalities and recovery rates of CD45 and CD34 positive cells and colony forming unit recovery rates. RESULTS: No single cryoprotective solution being significantly superior regarding all cell qualities and recovery rates could be identified. However, mixing approximately 5% DMSO with hydroxyethyl starch with a molecular weight of 450,000 Dalton showed better results for most qualities examined than DMSO alone, especially when looking at cord blood derived stem cells. CONCLUSIONS: There might not be an all-in-one cryoprotective solution suitable for every purpose regarding the cryopreservation of stem cell concentrates produced from different cell sources. However, when trying to reduce the DMSO amount used, hydroxyethyl starch of a molecular weight of 450,000 Dalton is a suitable option.
EVALuna2:32784

Correlation of the hypotonic shock response and extent of shape change with the new ThromboLUX (TM) - Kraemer, L.; Raczat, Tatjana; Weiss, D. R.; Strobel, Joachim; Eckstein, Reinhold; Ringwald, J. (Vox Sanguinis, 2015)
ThromboLUX (TLX)-Score was compared with hypotonic shock response (HSR) and extent of shape change (ESC) in 99 samples from 42 platelet concentrates. Tests were performed in parallel and duplicate. Mean values for TLX Score, HSR and ESC were 30.3 ± 3.8%, 69.0 ± 12.2% and 23.2 ± 4.9%, respectively. We found no significant correlation between TLX Score and HSR or ESC (r = -0.158, P = 0.118 and r = -115, P = 0.255, respectively), whereas HSR and ESC correlated significantly (r = 0.351, P < 0.001). As TLX Score did not show significant correlation with HSR and ESC, the value of TLX for platelet quality testing remains unclear. Studies comparing these parameters with transfusion outcome are needed.
EVALuna2:15993

Depletion of donor-specific anti-HLA A2 alloantibodies in a hematopoietic cell transplant recipient using directed mismatched platelet transfusions - Spriewald, Bernd M.; Bach, Christian; Zingsem, Jürgen; Strobel, Joachim; Winkler, Jürgen; Mackensen, Andreas; Rösler, Wolf (Bone Marrow Transplantation, 2018)
EVALuna2:34275

First comparative analysis concerning the plasma platelet contamination during MNC collection - Pfeiffer, Hella; Achenbach, Susanne; Strobel, Joachim; Zimmermann, Robert; Eckstein, Reinhold; Strasser, Erwin (Transfusion and Apheresis Science, 2017)
BACKGROUND AND OBJECTIVES: Monocytes can be cultured into dendritic cells with addition of autologous plasma, which is highly prone to platelet contamination due to the apheresis process. Since platelets affect the maturation process of monocytes into dendritic cells and might even lead to a diminished harvest of dendritic cells, it is very important to reduce the platelet contamination. A new collection device (Spectra Optia) was analyzed, compared to two established devices (COM.TEC, Cobe Spectra) and evaluated regarding the potential generation of source plasma. MATERIALS AND METHODS: Concurrent plasma collected during leukapheresis was analyzed for residual cell contamination in a prospective study with the new Spectra Optia apheresis device (n=24) and was compared with COM.TEC and Cobe Spectra data (retrospective analysis, n=72). Donor pre-donation counts of platelets were analyzed for their predictive value of contaminating PLTs in plasma harvests. RESULTS: The newest apheresis device showed the lowest residual platelet count of the collected concurrent plasma (median 3.50×109/l) independent of pre-donation counts. The other two devices and sets had a higher platelet contamination. The contamination of the plasma with leukocytes was very low (only 2.0% were higher than 0.5×109/l). CONCLUSIONS: This study showed a significant reduction of platelet contamination of the concurrent plasma collected with the new Spectra Optia device. This plasma product with low residual platelets and leukocytes might also be used as plasma for fractionation.
EVALuna2:32782

Functional characterization of CD34(+) cells from cryopreserved apheresis of patients with bone marrow-infiltrating malignancies - Wendland, Kerstin; Petkovic, S.; Aigner, Michael; Strobel, Joachim; Müller, Fabian (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

GMP-production of purified human B lymphocytes for the adoptive transfer in patients after allogeneic hematopoietic stem cell transplantation - Tittlbach, Hannes; Schneider, Andrea; Strobel, Joachim; Zimmermann, Robert; Maas, Stefanie; Gebhardt, Bernd; Rauser, Georg; Mach, Michael; Mackensen, Andreas; Winkler, Thomas; Winkler, Jürgen (Journal of Translational Medicine, 2017)
We have recently shown that memory B cells from murine CMV immune donor animals adoptively transferred into immunodeficient mice were highly effective in protecting from a viral infection indicating a therapeutic potential of virus specific memory B cells. These preclinical data provided evidence that a cell-based strategy supporting the humoral immune response might be effective in a clinical setting of immunodeficiency after allogeneic hematopoietic stem cell transplantation. As adoptive transfer of B cells has not been used before in a clinical setting it was necessary to establish a technology for the generation of good manufacturing practice (GMP)-grade B cell products.Starting from the leukapheresis product of healthy blood donors, B cells were purified by two different separation strategies using GMP-grade microbeads and the CliniMACS system. A one-step protocol was used for positive enrichment of B lymphocytes with anti-CD19 microbeads. In a two-step enrichment protocol, first T lymphocytes were depleted by anti-CD3 microbeads and the remaining fraction was positively selected by anti-CD19 microbeads.The purity and recovery after enrichment of B lymphocytes from the leukapheresis material in both separations strategies was not statistically different. However, contamination of the B-cell product with T cells was significantly lower after the two-step protocol (0.16%, range 0.01-0.43% after two-step separation and 0.55%, range 0.28-0.85% after one-step separation, p < 0.05). Therefore, a combined CD3 depletion and CD19 enrichment was used for the production of GMP-conform B-cell products from the leukapheresis material of 17 healthy stem cell donors. The absolute B-cell numbers obtained in the final product was 4.70 ± 3.64 × 108 with a purity of 95.98 ± 3.31% B lymphocytes and a recovery of 18.9 ± 10.6%. Importantly, the contamination with CD3+ T cells was extremely low in the final B- cell products (0.10 ± 0.20%). Purified B cells exhibited normal antibody production after in vitro stimulation and showed excellent viability after cryopreservation.A GMP-grade B-cell product can be obtained with high purity and very low T-cell contamination using the two-step enrichment protocol based on CliniMACS® technology.
EVALuna2:25773

HPA Frequencies in the Syrian Population - Hauck-Dlimi, Barbara; Damrah, Nouraldin; Achenbach, Susanne; Zimmermann, Robert; Zingsem, Jürgen; Ott, Stephan; Strobel, Joachim (Clinical Laboratory, 2019)
Background: Exposure to allogenic Human Platelet Antigens (HPAs) can lead to antibody formation causing different immunological reactions. Frequencies of common HPA antigens differ between ethnic groups and should be known to calculate potential alloimmunization risk. Syrian refugees are the largest group of applicants for asylum in Germany in 2017. However, no study on HPA antigen frequencies in the Syrian population exists.
CRIS-Team WoS Importer:2019-03-22

Immunophenotypes and Targets of clonally expanded T Cells in the Bone Marrow of Patients with acquired Aplastic Anemia - Ben Hamza, A.; Welters, C.; Bruggemann, M.; Dietze, K.; Bullinger, L.; Brummendorf, T. H.; Winkler, Thomas; Strobel, Joachim; Hackstein, Holger; Dornmair, K.; Beier, F.; Hansmann, L. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Influence of Duration and Temperature of Transport and Storage Prior to Processing on Cell Quality of Cord Blood Units - A German Experience - Strobel, Joachim; Brenner, Lukas; Zimmermann, Robert; Weiss, Dominik; Zingsem, Jürgen; Eckstein, Reinhold; Weisbach, Volker Günter (Clinical Laboratory, 2015)
In Germany, cord blood needs to be transported to the processing facility to be processed and cryopreserved within 48 hours after collection according to national guidelines. During that time, a temperature of 22 ± 4 degrees C must be maintained. The purpose of this study was to analyse the influence of temperature during transport and storage prior to processing and cryopreservation on stem cells in 2460 both autologous and allogeneic umbilical cord blood samples.Total and viable CD45+ cells, total and viable CD34+ cells, and mononuclear cells (MNC) of cord blood and resulting leucocyte concentrate both before and after freezing were analysed by flow cytometry. Transport protocols and the records of temperature measuring chips used in transport were evaluated in order to analyse how long each unit was exposed to which temperature ranges.On average, the cord blood preparations were delivered within 16.4 ± 6.3 hours. No cord blood was delivered and processed later than 48 hours after donation. Temperature of transport and storage before processing had minor but sometimes significant effects on cell viability. A temperature range of 20 - 24 degrees C showed best survival rates for CD34+ cells and highest colony forming potential.The temperature prior to processing has little yet sometimes significant effects on cell viability in stem cell concentrates prepared from cord blood. However, the absolute differences in cell viabilities are quite small. Therefore, the effect is clinically negligible in a range from 4 degrees C to 28 degrees C if cryopreservation is done within 48 hours.
EVALuna2:15998

Influence of early irradiation on in vitro red blood cell (RBC) storage variables of leucoreduced RBCs in additive solution SAG-M - Hauck-Dlimi, Barbara; Braun, Timm; Eckstein, Reinhold; Strobel, Joachim; Zimmermann, Rüdiger (Vox Sanguinis, 2016)
The only accepted way to avoid transfusion-associated graft-versus-host disease is irradiation of blood components. With respect to irradiation and associated storage time, different recommendations exist. We examined early irradiated (day +3) leucoreduced red blood cell units for irradiation-associated damages during storage.We studied 80 leucoreduced units from two manufacturers. All RBCs were stored in the additive solution saline-adenine-glucose-mannitol (SAG-M) and leucoreduced on collection day. Forty components were irradiated on day +3 with 30 Gy, 40 served as non-irradiated controls. Samples were drawn and analysed from these 80 units on days +3, +7, +14, +21, +28, +35 and +42.From day +14, there was a significant difference in the in vitro haemolysis rate between the non-irradiated and the irradiated components. Two of the irradiated units showed a haemolysis rate over the recommended limit of 0·8% on day +42. Potassium and lactate dehydrogenase activity increased faster in irradiated groups during storage.Our findings show that leucoreduced RBCs which are irradiated early after collection show an obvious radiation damage over storage period. Interestingly, on days +28, +35 and +42 the quality of RBCs which were irradiated on day +3 was nearly identical to the quality of RBCs which were irradiated on day +14 in a former series. Early irradiation does not cause more damage of RBCs during subsequent storage than irradiation on day +14. The maximum storage period of irradiated RBCs should remain restricted to 28 days from collection, however independently from the day of irradiation within this period.
EVALuna2:15994

Influence of Irradiation on Leukodepleted Small Unit Red Blood Cell (RBC) Bags for Infant Transfusion in Additive Solution SAG-M - Hauck-Dlimi, Barbara; Schiffer, Katharina; Eckstein, Reinhold; Strobel, Joachim; Zimmermann, Robert (Clinical Laboratory, 2016)
BACKGROUND: To reduce transfusion-associated graft-versus-host disease irradiation of blood products is widely accepted. There is little data about the effect of gamma-irradiation on leukoreduced RBCs stored in SAG-M that are subdivided for use in transfusion to preterm infants and small children. METHODS: We studied 30 leukoreduced SAG-M preserved RBC bags. All RBCs were leukoreduced on the collection day. The 30 units were divided into two groups. Every unit was divided into three bags. One of these bags served as nonirradiated control (group 1A, group 2A), the other two were gamma-irradiated at different times. In vitro evaluation of irradiated and nonirradiated units was performed on the days +3, +7, +14, +21, and +28 from the day of collection. RESULTS: Gamma irradiation induced a higher increase of extracellular hemoglobin, LDH, and potassium than non-irradiated storage over the time. No irradiated or non-irradiated unit showed a hemolysis rate over the recommended limit of 0.8% over the 28 day period. CONCLUSIONS: Our findings show that subdivision of RBCs does not have an appreciable influence on the storage of leukoreduced, irradiated RBCs in AS SAG-M. Our "worst case scenario" was irradiation on day +3 after donation and subsequent storage until day +28. Especially for infant use, it is important to have the possibility to irradiate even late after donation, because this procedure offers the possibility to use one RBC bag over a longer period of time and to reduce the donor exposure for infants. Therefore, subdivided leukoreduced RBCs can be safely irradiated until day +14 and subsequently stored until day +28 after donation.
EVALuna2:32775

Measuring Lymphocyte Proliferation in Response to Specific Antigen and Mitogen Stimuli Using Flow Cytometry - Heider, Stefan; Strobel, Joachim; Mempel, Wolfgang; Eckstein, Reinhold; Weisbach, Volker Günter (Clinical Laboratory, 2016)
BACKGROUND: We present a multivariate test system using flow cytometry after in-vitro lymphocyte stimulation using 5 mitogens and 7 antigens to describe in-vitro immunofunction. METHODS: The present work is a crucial step towards establishing a simple, CFSE-based, multivariate test system that can describe the dynamics of stimulus-induced lymphocyte proliferation with considerably more precision than is possible with the radionucleotide method using 3H-thymidine. Using multicolour flow cytometry, our method allows additional phenotyping of the proliferating cells and quantifies the proliferation behaviour by precisely resolving daughter generations and determining the precursor frequency. CONCLUSIONS: Taking the calculated apoptosis parameters into account not only provides additional information about the stimulus-specific response behaviour but also improves the validity of the commonly used proliferation indices. Not only can we confirm previous findings that healthy people have marked differences in a multivariate test system in terms of the individual in-vitro reactivity to various stimuli but also substantiate that the response pattern of an individual is remarkably constant. In follow-up studies we can show for the first time that the results of immunofunctional testing do not change over a period of at least 6 months and appear to be an inherent characteristic of the individual and thus possibly have a genetic basis.
EVALuna2:32777

Quality of Clotting Factor Activity in Fresh Frozen Plasma at Thaw with a Microwave System and after Storage at 4 degrees C for 48 Hours - Kuta, Piotr; Hauck-Dlimi, Barbara; Strobel, Joachim; Zimmermann, Robert; Eckstein, Reinhold (Clinical Laboratory, 2016)
BACKGROUND: Uncontrolled hemorrhage in polytrauma patients usually results in rapid need of blood products. Despite the shorter thawing times of microwave devices for heating fresh frozen plasma (FFP), their use has remained controversial, and just a few laboratory analyses have been published on this topic. The aim of this study was to analyse the quality of clotting factors immediately after thawing FFP with a microwave device and after 48-hour post thaw storage at 4 degrees C. METHODS: 24 FFP units of all four ABO blood groups (six of each blood group) were thawed with a Transfusio-therm 2000 and later stored at 4 degrees C for 48 hours. Samples were drawn aseptically and investigated on various clotting factors and protein proteases (fibrinogen, antithrombin, FII, FV, FVII, FVIII, FIX, FX, FXI, FXIII, vWF antigen and activity, protein S, and protein C) using standard coagulation and chromogenic assays immediately after thawing and again after a 48-hour storage period at 4 degrees C. All units were tested for both anaerobic and aerobic microbial contamination using standard operating procedures immediately after thawing. RESULTS: After thawing, all coagulation factors and protein protease activities were within normal ranges. Blood group O individuals had approximately 25% lower plasma levels of vWF antigen and activity. After a 48-hour storage period at 4 degrees C, FVIII and FIX activities declined significantly in all blood groups, whereas the remaining clotting factors remained comparably stable. CONCLUSIONS: Immediately after rapid thawing using a microwave system, all FFP units contained adequate coagulation factor activities to maintain hemostatic activity at the time of product thaw. The post thaw refrigerated storage caused an anticipated decrease in factor VIII and IX activities, but retained normal coagulation factor levels of many plasma proteins. Therefore we conclude that the Transfusio-therm 2000 has no clinically significant influence on the activity of clotting factors and plasma proteases in FFP units.
EVALuna2:32776

T-cell subsets in autologous and allogeneic peripheral blood stem cell concentrates - Strobel, Joachim; Möllmer, Ina; Zingsem, Jürgen; Hauck-Dlimi, Barbara; Eckstein, Reinhold; Strasser, Erwin (Vox Sanguinis, 2015)
Regulatory T cells (Tregs) and other T-cell subsets are of importance in the setting of autologous and allogeneic stem cell transplantations. We conducted a study to assess the content of peripheral blood stem cell concentrates and related apheresis parameters in the autologous and allogeneic setting.We characterized 53 donors, patients and peripheral blood stem cell concentrates (PBSC) regarding the content of CD45(+) cells, lymphocytes, CD3(+) cells, CD3(+) CD4(+) T cells, CD3(+) CD4(+) CD25(+) T cells, CD3(+) CD4(+) CD25(+) CD127(low/negative) Tregs and CD34(+) cells and calculated cell yields, recruitment factors and collection efficiency for all cell types. We compared allogeneic data with autologous data.Autologous PBSC show significantly lower concentrations of T-cell subsets compared to allogeneic PBSC (17,112/?l CD4(+), 14,858/?l CD4(+) CD25(+) and 1579/?l CD3(+) CD4(+) CD25(+) CD127(low/negative) Tregs in autologous compared to 65,539/?l CD4(+), 44,208(+) /?l CD4(+) CD25(+) and 5040/?l CD3(+) CD4(+) CD25(+) CD127(low/negative) Tregs in allogeneic PBSC, respectively), in contrast to CD34(+) concentrations (5342/?l CD34(+) in autologous compared to 2367/?l CD34(+) in allogeneic PBSC, respectively). Accordantly, all T-cell yields are lower in the autologous setting compared to allogeneic PBSC. However, recruitment factor and collection efficiency of all cell types are higher in autologous compared to allogeneic PBSC, but not all parameters differ significantly when groups are compared.T-cell subsets and especially Tregs are a substantial part of PBSC transplantation, as considerable recruitment during apheresis occurs. In large volume apheresis, the collection efficiency of Treg is comparable to that of CD34(+) cells, while recruitment factors are even higher.
EVALuna2:15982

The novel allele, HLA-B*08:113, identified in a German cord blood donor and his mother - Strobel, Joachim; Ringwald, J.; Hauck-Dlimi, B.; Eckstein, Reinhold; Zingsem, Jürgen (Tissue Antigens, 2014)
The novel allele HLA-B*08:113 identified in two related individuals of Caucasian origin is described.
EVALuna2:15979

Transfusion-related alloimmune neutropenia with no pulmonary complications: one donor-five cases - Hauck-Dlimi, Barbara; Ruppel, Renate; Zimmermann, Robert; Strobel, Joachim; Reil, Angelika; Eckstein, Reinhold; Zingsem, Jürgen (Transfusion, 2016)
Neutrophil alloantibodies are well-known triggers of transfusion-related acute lung injury (TRALI) and also cause immune neutropenia. Alloimmune neutropenia due to transfusion is an isolated phenomenon that is only rarely identified. Its incidence is specified in the literature as being less than one in 10,000 transfused plasma-containing units. We expect that this phenomenon is underreported.We observed five cases of alloimmune neutropenia with no respiratory complications with only one case initially reported as a suspected transfusion reaction. The other four cases were detected in the course of the subsequent lookback investigation.The first case was reported as a potential transfusion reaction when a female patient showed a decrease in the white blood cell count after a platelet (PLT) transfusion. Examinations of the donor blood revealed an antibody against the human neutrophil antigen HNA-1b; the recipient was typed HNA-1b positive and HNA-1a negative. After examining the blood counts of other patients who previously received PLT concentrates from the same donor, we identified four other patients with an unreported decrease in the leukocyte and/or granulocyte count of more than approximately 50% after transfusion.HNA antibodies are generally regarded as potential triggers of TRALI. Here we describe an HNA antibody that reproducibly caused transfusion-related neutropenia only without pulmonary complications. Factors predisposing patients to TRALI development are widely discussed. Our case suggests that antibody characteristics are also relevant in the development of TRALI. Current measures to prevent TRALI should also prevent transfusion-related alloimmune neutropenia.
EVALuna2:15990